Low-frequency (ELF–VLF) radio atmospherics study at the Ukrainian Antarctic Akademik Vernadsky station - A. V. Shvets; A. P. Nickolaenko; A. V. Koloskov; Yu. M. Yampolsky; O. V. Budanov; A. A. Shvets (Ukrainian Antarctic Journal, 2019)
This paper describes the results of the atmospherics measurements in the extremely low-frequency (ELF) and very low-frequency (VLF) frequency ranges performed at the Akademik Vernadsky station (64.26W; 65.25S) during February–April 2019. The main objective of the study was the implementation of a single-site technique for monitoring the lower ionosphere parameters and locating globally distributed powerful lightning discharges. Methods. The receiving and analyzing VLF complex was used at the station to record two horizontal magnetic and vertical electric components of atmospherics in the frequency range 750 Hz – 24 kHz. A single-site lightning location method is based on the analysis of tweek-atmospherics (tweeks).It was implemented in the receiving system software. This allowed obtaining real-time information about lightning position, height and electron density variations in the lower ionosphere.The records of VLF atmospherics were synchronized via GPS timestamps with records of ELF transients resulted from globally distributed powerful lightning discharges. Results of analysis of tweeks recorded at the Akademik Vernadsky station indicates that lightning discharges are registered at distances from 2,000 km to about 10,000 km within the azimuthal sector, covering almost the entire South American continent, southern Africa and the Gulf of Guinea. Practically, no tweeks from the Pacific were recorded. This can be attributed to the non-reciprocity of attenuation of radio waves propagating in the west-east and east-west directions. In addition to the fundamental mode, we observed also the second and higher order modes of tweeks. This allowed estimating the lower boundary altitude and the electron density in the lower ionosphere. We demonstrated the advantages of simultaneous recordings of VLF atmospherics and ELF transients. Employing the vertical electric and two horizontal magnetic components measured by the VLF complex allowed for more accurate and unambiguous determining the source azimuth and resolving polarity of the charge transfer in the parent lightning discharges. Combining the ELF and VLF records, we can determine a distance to lightning and, then, parameters of the current moment of the lightning discharge. Conclusions. The performed experimental studies has shown the prospect of further combined ELF–VLF monitoring at the Akademik Vernadsky station, enabling detection of globally distributed powerful lightning discharges and changes in the lower ionosphere related to various phenomena of space weather, atmospheric and of terrestrial origin.